2012
DOI: 10.1093/nar/gks463
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exosomes can deliver exogenous short interfering RNA to monocytes and lymphocytes

Abstract: Despite the promise of RNA interference (RNAi) and its potential, e.g. for use in cancer therapy, several technical obstacles must first be overcome. The major hurdle of RNAi-based therapeutics is to deliver nucleic acids across the cell’s plasma membrane. This study demonstrates that exosome vesicles derived from humans can deliver short interfering RNA (siRNA) to human mononuclear blood cells. Exosomes are nano-sized vesicles of endocytic origin that are involved in cell-to-cell communication, i.e. antigen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
455
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(484 citation statements)
references
References 31 publications
8
455
2
2
Order By: Relevance
“…Leaders in this research area, such as Alvarez‐Erviti et al, have transferred siRNA into EVs via electroporation; subsequent experiments have demonstrated that these electroporated EVs could significantly inhibit expression of the target gene ( Figure 9 ). 20 Electroporation to generate siRNA‐loaded EVs was successfully verified by follow‐up studies 119, 120. However, it appears that electroporation might not be efficacious for transferring all types of RNA directly into EVs without modifying the “source cells.”107 Simple electroporation might not be sufficiently efficient, and more in‐depth studies are needed 121.…”
Section: Modular Design Of Internal Contentsmentioning
confidence: 99%
“…Leaders in this research area, such as Alvarez‐Erviti et al, have transferred siRNA into EVs via electroporation; subsequent experiments have demonstrated that these electroporated EVs could significantly inhibit expression of the target gene ( Figure 9 ). 20 Electroporation to generate siRNA‐loaded EVs was successfully verified by follow‐up studies 119, 120. However, it appears that electroporation might not be efficacious for transferring all types of RNA directly into EVs without modifying the “source cells.”107 Simple electroporation might not be sufficiently efficient, and more in‐depth studies are needed 121.…”
Section: Modular Design Of Internal Contentsmentioning
confidence: 99%
“…Load siRNA to MAPK-1 into exosomes Suppress MAPK-1 in monocytes and lymphocytes [24] Mouse M12.4 B lymphocyte…”
Section: Electroporation Of Hydrophilic Cargomentioning
confidence: 99%
“…Wahlgren et al compared the efficiency of two methods for loading plasmaderived exosomes with siRNA to MAPK-1 [24]. The two loading methods included chemical transfection using HiPerFect commercial transfection reagent and EP.…”
Section: Encapsulating Cargo In Exosomesmentioning
confidence: 99%
“…Jian-Jun Wang 1 , Ze-You Wang 2 , Rui Chen 3 , Jing Xiong 4 , Yong-Liang Yao 1 , JianHong Wu 1 , Guang-Xin Li 3 * intercellular delivery of endogenous proteins and nucleic acids, and can also deliver exogenous pharmaceutical proteins and nucleic acids such as mRNAs, microRNAs (miRNAs) and siRNAs (Wahlgren et al, 2012;Chen et al, 2014). Exosome secretion of microvesicles transporting miRNAs, mRNAs, and proteins through bodily fluids facilitates intercellular communication and can elicit an immune response (McDonald et al, 2014).…”
Section: Macrophage-secreted Exosomes Delivering Mirna-21 Inhibitor Cmentioning
confidence: 99%